The use of a non-lethal tool for evaluating toxicological hazard of organochlorine contaminants in Mediterranean cetaceans: new data 10 years after the first paper published in MPB - FOSSI, M. C.; MARSILI, L.; NERI, G.; NATOLI, A.; POLITI, E.; PANIGADA, S. (Marine Pollution Bulletin, 2003)
In the Mediterranean Sea, top predators, and particularly cetacean odontocetes, accumulate high concentrations of organochlorine contaminants and toxic metals, incurring high toxicological risk. In this paper we investigate the use of the skin biopsies as a non-lethal tool for evaluating toxicological hazard of organochlorines in Mediterranean cetaceans, presenting new data 10 years after the paper published by Fossi and co-workers [Mar. Poll. Bull. 24 (9) (1992) 459] in which this new methodology was first presented. Some organochlorine compounds, now with worldwide distribution, are known as endocrine disrupting chemicals (EDCs). Here the unexplored hypothesis that Mediterranean cetaceans are potentially at risk due to organochlorines with endocrine disrupting capacity is investigated. High concentrations of DDT metabolites and PCB congeners (known as EDCs) were found in the different Mediterranean species (Stenella coeruleoalba, Delphinus delphis, Tursiops truncatus and Balaenoptera physalus). In this paper we also propose benzo(a)pyrene monooxygenase (BPMO) activity in marine mammal skin biopsies (non-lethal biomarker) as a potential indicator of exposure to organochlorines, with special reference to the compounds with endocrine disrupting capacity. A statistically significant correlation was found between BPMO activity and organochlorine levels (DDTs, pp'DDT, op'DDT, PCBs and PCB99) in skin biopsies of males of B. physalus. Moreover a statistical correlation was also found between BPMO activity and DDT levels in skin biopsies of the endangered Mediterranean population of D. delphis. These results suggest that BPMO induction may be an early sign of exposure to organochlorine EDCs and can be used for periodic monitoring of Mediterranean marine mammal toxicological status.